TRANSFORMING KINATAH NAGASASRA AS A BATIK MOTIFS FOR CASUAL CLOTHES - mellynada putri, casi; saputra, andi taslim (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2024)
This work creation was inspired by the shape of Kinatah Nagasasra, a name of dhapur (physical form) of a Kris. Such a dapur is characterized by the presence of decoration in the form of dragon as a Kinatah on the surface of the Kris blade. The characteristics of Nagasasra are having a kinatah in the form of crowned dragon, having a thousand scales on its body, and having a jamang (head ornament worn on the forehead). This Kris blade has visual meaning in the form of symbols representing characteristics of a leader. This study aims at exploring and stylizing the shape of Kinatah Nagasasra and using it in creating handmade batik on the casual wear. The creation of this work employed the   art creation method by collecting data from literature as well as previous designs and embodiments.  Handmade batiks technique was used in the creation process by using   primissima cotton fabric and remasol (coloring matter) as raw materials. Handmade batik technique that is used is dipping technique. The color chosen is the color preferred by consumers aged 18-35 years.  The resulting work consists of four dresses and is entitled UPANGGA RADMILA. Each of dress has also its own title, namely PANDITA, PARAHITA, PRABALA, PRASANTI. The designers hope that this work can help to socialize good characteristics of leader through symbols in it.  The characteristics consists of prioritizing the welfare of members, the awareness that power is a trust, being able to protect and prosper members, and being a role model to the members.